Birth dates of men with cancer of the testis. Issue 3 (September 1985) - Knox, E G; Cummins, C
Abstract : A recent rise in the incidence of cancer of the testis in affluent countries and affluent social strata suggests either an iatrogenic effect analogous with adenocarcinoma of the vagina or a prenatal infection analogous with congenital rubella syndrome. Three samples were assembled, two based on registration and one on death certification, and dates of birth were examined for the presence of steps, cycles, and irregular clusters. There was no evidence of a sudden step, and only equivocal evidence of clustering, but there was strong evidence of a temporal cycle. The cycle has a four-month period, analogous with a school-term-related cyclical component identified in other diseases. A prenatal infection is strongly suggested, but the pattern enables us to exclude many of the common childhood infectious fevers.